INTEGRATING GAMIFIED STRATEGIES IN LANGUAGE LEARNING: THE EFFECTIVENESS OF SNAKES AND LADDERS FOR POETRY WRITING - Tahir, Moh; Syamsuddin, Syamsuddin; Gazali, Gazali; Suputra, Gusti Ketut Alit; Efendi, Efendi; Mainjoe, Nurul Hikma Vilia; Pramudita, Reti Alit (Universitas Labuhanbatu, 2025)
Purpose—This study investigates the effectiveness of integrating the Snake and Ladder game as a gamified learning medium to enhance students' engagement and creativity in poetry writing. The study discusses the limitations of the traditional teacher-centered approach, which often fails to involve students or foster creativity, by proposing a gamified strategy specifically designed for middle school learners. Methodology- Using a qualitative case study, this study was conducted on 28 students of the eighth grade at class VIII-A, SMP Negeri 1 Banawa Tengah, Sulawesi Tengah, Indonesia. This study involved two learning sessions where students were involved in a modified Snakes and Ladders game, which combined the tasks related to the poetry, such as composing verses and identifying poetic devices—the data collected from class observation, students’ poetry submissions, and teacher reflections. Thematic analysis measured students' engagement, creativity, and collaborative outcomes.Findings- The findings show that 70% of students actively engaged and showed creative expression in their poetry, integrating the main elements of poetry effectively. There are 25% who show creativity, even in the face of a lack of engagement in the game, while 5% actively engage in the game but find it challenging to compose poetry. This study highlights the potential of gamified learning to grow teamwork, critical thinking, and a dynamic learning atmosphere, transforming poetry writing from a passive task and a monotone to an interactive and fun experience.Contribution—This study contributes to the growing number of gamified learning in education and its impact on poetry writing. It offers valuable knowledge for educators, curriculum designers, and policy makers, showing the adaptability of gamified learning in the diverse context of education and providing a replicable model to be integrated creatively into poetry writing tasks in language learning.